2021
DOI: 10.1088/1361-648x/abe606
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained model of a nanoscale-segregated ionic liquid for simulations of low-temperature structure and dynamics

Abstract: We perform molecular dynamics simulations to study the structure and dynamics of the ionic liquid [Omim][TFSI] in a broad temperature range. A particular focus is the progressing nanoscale segregation into polar and nonpolar regions upon cooling. As this analysis requires simulations of large systems for long times, we use the iterative Boltzmann inversion method to develop a new coarse-grained (CG) model from a successful all-atom (AA) model. We show that the properties are similar for both levels of descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…From the point of view of time bridging, both the speedup and the telescoping are beneficial, as they allow one to access later time scales in CG simulations and study processes on different time scales simultaneously in one simulation. One of the earliest and still widely and successfully used approaches to dynamic coarse-graining has been to simply take advantage of this effect, determine the speedup factor of the process of interest, and use this to map the CG dynamics on real dynamics, taking into account that the speedup factor might be different for different processes and/or components .…”
Section: Scale-bridging Strategiesmentioning
confidence: 99%
“…From the point of view of time bridging, both the speedup and the telescoping are beneficial, as they allow one to access later time scales in CG simulations and study processes on different time scales simultaneously in one simulation. One of the earliest and still widely and successfully used approaches to dynamic coarse-graining has been to simply take advantage of this effect, determine the speedup factor of the process of interest, and use this to map the CG dynamics on real dynamics, taking into account that the speedup factor might be different for different processes and/or components .…”
Section: Scale-bridging Strategiesmentioning
confidence: 99%
“…The articles in this special issue illustrate the progress that has been made in the field of multiscale modelling of soft matter in recent years, as well as the many remaining challenges and open questions. They also demonstrate the potential of multiscale simulations for obtaining insights into complex systems and processes, such as nanoscale-segregated ionic liquids [17], high performance rubber materials [28], emergent properties of active or responsive colloids [11,23], or controlled nanoparticle growth [29,30].…”
mentioning
confidence: 88%
“…However, in studies of kinetic pathways, it is important that at least the order of time scales remains the same. Kloth et al [17] and Rudzinski et al [18] have examined this for ionic liquids and found that accurate structural coarse-graining also improves the dynamic properties of CG models in regular molecular dynamics. Li et al [20] propose a method to adjust relative time scales in extremely CG Brownian polymer models by adjusting internal friction parameters.…”
mentioning
confidence: 99%
“…MD simulations have been extensively used to investigate the structural and physicochemical characteristics of ionic liquids and surfactants in recent years. [22][23][24][25][26][27][28][29] Some in silico studies were focused on the aggregation properties of ILs in different solutions and interfaces in terms of the structure, shape, and size of micelles. 22,23,[30][31][32] To the best of our knowledge, only a few reports are available on the effective factors that influence the nature of SAILs' self-assembly and their morphology.…”
Section: Introductionmentioning
confidence: 99%